2011
DOI: 10.1093/ecam/neq024
|View full text |Cite
|
Sign up to set email alerts
|

Bio‐Prospecting of a Few Brown Seaweeds for Their Cytotoxic and Antioxidant Activities

Abstract: Methanolic extracts (MEs) of seven brown seaweeds occurring in the Indian coastal waters were screened for their cytotoxic and antioxidant properties following various assays. The methanolic extracts of seaweeds in the order of Dictyopteris australis > Spatoglossum variabile > Stoechospermum marginatum > Spatoglossum aspermum showed significant cytotoxic activity. A very high DPPH radical scavenging activity was exhibited by the methanolic extracts prepared from St. marginatum, Padina tetrastromatica, Dictyopt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
0
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(50 citation statements)
references
References 49 publications
2
41
0
7
Order By: Relevance
“…High levels of TPC in brown marine algae are expected, considering reports indicating they are rich sources in fucoxanthin (D'Orazio et al, 2012) and phlorotannins (Wang et al, 2012). Similar results were also described by Wang et al (2009) (Vinayak, Sabu, & Chatterji, 2011), whose values were very similar to the methanolic extracts from the brown seaweeds D. dichotoma and S. vulgare analyzed in this study.…”
Section: Tpc Valuessupporting
confidence: 88%
See 1 more Smart Citation
“…High levels of TPC in brown marine algae are expected, considering reports indicating they are rich sources in fucoxanthin (D'Orazio et al, 2012) and phlorotannins (Wang et al, 2012). Similar results were also described by Wang et al (2009) (Vinayak, Sabu, & Chatterji, 2011), whose values were very similar to the methanolic extracts from the brown seaweeds D. dichotoma and S. vulgare analyzed in this study.…”
Section: Tpc Valuessupporting
confidence: 88%
“…These results were higher than those obtained for A. multifida and C. crenulata, which were from 50 (100 μg mL -1 ) to 400 (12.5 μg mL -1 ) times less concentrated. Among the methanol extracts of brown seaweeds analyzed by Vinayak et al (2011), Dictyopteris australis showed FIC approximately 16% higher than the extracts of Dictyota dichotoma and Sargassum vulgare at 100 mg L -1…”
Section: Ferrous Ion Chelating Activity (Fic)mentioning
confidence: 94%
“…Produced endogenously in cellular tissues, reactive oxygen species (ROS), such as the hydroxyl radical (OH˙), superoxide radical (O 2ˉ) , hydroperoxyl radical (HO 2˙) , hydrogen peroxide (H 2 O 2 ) and singlet oxygen ( dysfunction, muscular dystrophy, ischemia, tissue damage and neurological disorders (Vinayak et al 2011a, b, Wang et al 2011, Yangthong et al 2009). …”
Section: Introductionmentioning
confidence: 99%
“…Among the tested brown seaweeds, Sargassum polycystum exhibited the better antimicrobial activity that has potentially used as antimicrobial agent and as natural immunostimulant with aquaculture industry for the treatment of microbial diseases and improvement of the health status of commercially important aquaculture species. minerals, vitamins, essential amino acids, fatty acid, dietary fiber and carbohydrates and as long as food, agricultural fertilizers and drugs have been used (Dawczynski et al, 2007), and the context of radical scavenging properties seaweeds possess natural antioxidants such as carotenoids, pigments, polyphenols, enzymes and diverse functional polysaccharides (Vinayak et al, 2011). The use of seaweeds are inexpensive than chemicals and antibiotics and have little effects on nature, humans and fish.…”
Section: Issn: 2319-7706 Volume 6 Number 2 (2017) Pp 1024-1037mentioning
confidence: 99%